Perbandingan Konsep Metafisik Imam Al-Ghazali dan Seyyed Hossein Nasr - Sari Haryati; Nasrun Harahap; Nuratika; Zainuddin (Kartika: Jurnal Studi Keislaman, 2026)
This article examines a comparative analysis of the metaphysical concepts of Imam al-Ghazālī and Seyyed Hossein Nasr by highlighting the fundamental similarities and differences in their thought. This study employs a qualitative method with a library research approach, drawing on major scholarly books and relevant academic journal articles. The findings indicate that both al-Ghazālī and Nasr position God as the Absolute Reality and reject materialistic views of reality. Al-Ghazālī developed his metaphysical framework within the context of classical Islamic thought to harmonize theology, philosophy, and Sufism while safeguarding doctrinal orthodoxy. Meanwhile, Nasr formulates metaphysics as a critique of modernity through the concepts of scientia sacra, the hierarchy of being, and the sacredness of nature. Differences in historical context lead to variations in intellectual orientation; however, both thinkers affirm that Islamic metaphysics carries significant epistemological, ethical, and spiritual implications. This article concludes that the metaphysical ideas of al-Ghazālī and Nasr are complementary in demonstrating the enduring relevance of Islamic metaphysics in addressing religious and human challenges across different eras